The Role of Automation in Modernizing Irrigation Practices and Smart Farming: A Comprehensive Review - Sanket S. Katte; Sanket U. Gaikar; Rushikesh J. Gujar; Kajal R. Chimane; Prof. Shruti Gour (International Journal of Electrical Machine Analysis and Design, 2024)
The development of a "Smart Farming Using Automation" system that functions in three modes—timer, soil moisture, and PH sensor—for the farmer's advantage is the focus of this study. An automated drip irrigation system with a PLC is described in this paper. Using sensors for soil moisture and pH. The soil moisture sensor's function is to calculate how much water is required for irrigation. A PLC uses the solenoid valve to control the water supply when the moisture content is either at the right level or lower. Depending on the pH level of the soil, a fertiliser supply system is also incorporated into the water irrigation system. This study focuses on the system of agriculture that can be used to control the parameters of an agricultural area. Observation from carrying out this study demonstrates effective use of water for crops, reduction in losses resulting from climate change, and appropriate application of fertiliser in the agricultural field. The Mitsubishi FX3 PLC platform is used to implement the suggested automation strategy in real time. The demand for efficient irrigation systems has increased due to water constraint and the desire for higher agricultural output. In this work, we suggest an automated drip irrigation system that precisely controls and manages the irrigation process using a PLC. The PLC is connected to a network of sensors that are integrated into the system to monitor temperature, humidity, soil moisture content, and weather. After processing the sensor data, the PLC applies pre-programmed logic-based programming to regulate the irrigation system's valve, solenoid valve, and other components.
Keywords: Automation; Mitsubishi FX 3 PLC; PH sensor; soil moisture sensor; solenoid valves